Carbon footprint assessment for academic institution: A UI greenmetric approach - Abdullah S.; Mansor A.A.; Ahmed A.N.; Napi N.N.L.M.; Ismail M. (International Journal of Scientific and Technology Research, 2023)
Climate change is a worldwide issue, caused by the emissions of Greenhouse Gases (GHG) of which the dominant contributor i s Carbon Dioxide (CO2). The amount of GHG produced by any higher institution can be quantified using carbon footprint (CF) estimation, of which the most established is UI GreenMetric carbon footprint approach. This study determine the CF at University Malaysia Terengganu, one of the public universities in Malaysia by quantifying 6 categories that are Setting and Infrastructure (SI), Energy and Climate Change (EC), Water (WR), Waste (WS), Transport (TR) and Educational (ED). Data was collected utilising primary and secondary data collection whereby primary data collection involves TR indicator for traffic volume. Other categories data were provided by the relevant authorities of UMT. Result shows a decreasing emission of CF for academic year 2017/2018 and 2018/2019; from 1212145.524 metric ton to 1209743.2 metric ton, respectively. This positive improvement is made possible by 2 approaches: employing correct technique of measurements plus verification of data and UMT top management sustainability plans and actions. However, there are 2 categories that need more attention for improvement i.e. WR (19%) and EC (17%). The findings from this study show a better achievement compared to previous year because of overestimated for TR indicator and unverified data calculation during secondary data collection. Outcome from this study increases UMT ranking from 13 to 6, out of 18 participated universities in Malaysia and the most important, it enables the university leaders to set up the eco-accommodating strategies and oversee social changes among the academic community. IJSTR 2019.